SISTEM INFORMASI KOST BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL STUDI KASUS : KOST DEVI - Zidane Anvio Putra (2023)
Higher education in the modern era demands more than mere classroom attendance; it requires a suitable living environment for students. Pembangunan Nasional Veteran Jakarta University faces challenges in providing affordable accommodation around the campus. The development of a web-based application is proposed as a solution to enhance the efficiency of searching for living spaces. This research focuses on leveraging technology to overcome information limitations for prospective tenants and property owners. The waterfall development method is employed to ensure structured progress through planning, analysis, design, implementation, testing, and maintenance stages. The research aims to design a web-based application to promote living spaces for Universitas Pembangunan Nasional Veteran Jakarta students. This application presents information on facilities, costs, and accommodation locations, addressing information barriers. The benefits of the research involve easier access for prospective tenants and marketing optimization for property owners. The study is expected to serve as a reference for developers of similar applications and contribute to the development of the waterfall method in software development. Thus, the research not only meets practical needs but also contributes to the broader development of information technology.